The Influence of Leadership and Work Discipline on the Performance of State Civil Apparatus at the UPTD Office of the South Sumatra Provincial Education Office - Leni Maryani; Yasir Arafat; Syaiful Eddy (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the influence of leadership and work discipline on the performance of the State Civil Apparatus (ASN) at the UPTD Office of the South Sumatra Provincial Education Office. Effective leadership and high work discipline are believed to be two important factors in improving ASN performance. This study uses a quantitative approach with a survey method. Data was collected through a questionnaire distributed to 60 ASN respondents at the UPTD office of the South Sumatra Provincial Education Office. The analysis technique used is multiple linear regression to test the simultaneous and partial influence of leadership and work discipline on ASN performance. The results of the study show that leadership and work discipline have a significant effect on ASN performance, both simultaneously and partially. The level of relationship between variables is included in the close category, with the contribution of the influence of independent variables on dependent variables included in the category is quite high.